Endovascular treatment of M2 dissecting aneurysm presenting with subarachnoid haemorrhage. (January 2014) - Kim, Sang Heum; Kim, Tae Gon; Cho, Kyung Gi; Chung, Sang Sup
Abstract A 63-year-old woman presented with a ruptured dissecting aneurysm (DA) at the right M2 region of the angular branches. This report describes a rare case of middle cerebral artery DA presenting with a subarachnoid haemorrhage (SAH); the patient was successfully treated with endovascular internal trapping of the DA, without a bypass surgery.